Chemical engineering design principles, practice, and economics of plant and process design - Towler, Gavin P. (Butterworth-Heinemann, 2013)
"Chemical Engineering Design is a complete course text for students of chemical engineering. Written for the Senior Design Course, and also suitable for introduction to chemical engineering courses, it covers the basics of unit operations and the latest aspects of process design, equipment selection, plant and operating economics, safety and loss prevention. It is a textbook that students will want to keep through their undergraduate education and on into their professional lives."--Publisher's website.
Includes index.
Keywords: Chemical engineering.; Production engineering.; elektronické knihy; electronic books